2022
DOI: 10.1186/s13104-022-06081-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage search for cancer susceptibility loci in a cohort of non BRCA1/2 families in Sri Lanka

Abstract: Objective Although linkage studies have been utilized for the identification of variants associated with cancer in the world, little is known about their role in non BRCA1/2 individuals in the Sri Lankans. Hence we performed linkage analysis to identify susceptibility loci related to the inherited risk of cancer in a cohort of Sri Lankans affected with hereditary breast cancer. The Illumina global screening array having 654,027 single nucleotide polymorphism markers was performed in four famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…EXOC1 is the gene exocyst complex component 1 and is involved in cell migration, similar to Sections 5 and 8 [ 42 ]. No literature was found that supports the connection between EXOC1 and CC; however, genetic mutations in EXOC1 have been associated with breast and cervical cancer [ 46 , 47 ]. Combining our experimental data and the literature evidence, EXOC1 may be inferred as a dark biomarker of mCC due to its involvement in cell migration processes, and transcriptomics may not be the ideal technology to investigate its functional roles.…”
Section: Resultsmentioning
confidence: 99%
“…EXOC1 is the gene exocyst complex component 1 and is involved in cell migration, similar to Sections 5 and 8 [ 42 ]. No literature was found that supports the connection between EXOC1 and CC; however, genetic mutations in EXOC1 have been associated with breast and cervical cancer [ 46 , 47 ]. Combining our experimental data and the literature evidence, EXOC1 may be inferred as a dark biomarker of mCC due to its involvement in cell migration processes, and transcriptomics may not be the ideal technology to investigate its functional roles.…”
Section: Resultsmentioning
confidence: 99%